2017 IEEE/ACM 10th International Workshop on Cooperative and Human Aspects of Software Engineering (CHASE) 2017
DOI: 10.1109/chase.2017.6
|View full text |Cite
|
Sign up to set email alerts
|

Intertemporal Choice: Decision Making and Time in Software Engineering

Abstract: Abstract-When making choices in software projects, engineers and other stakeholders engage in decision making that involves uncertain future outcomes. The concept of 'intertemporal choice' describes choices between outcomes at different times in the future. Short-sighted decisions with far-reaching effects are a long-standing cause of concern in the software profession.Common models to support decisions in software projects use concepts such as expected utility and discount factors to quantify future value and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 37 publications
0
6
0
Order By: Relevance
“…Examples of similarly structured questions seem common in SE. A second systematic review about studies of trade-off decisions in SE came to the same conclusion [13]. Again, data collection in empirical studies was predicated on the narrowly framed concepts of rationalistic decision making: factors, weights, ranking, and choice.…”
Section: The Normative Fallacy In Sementioning
confidence: 94%
See 1 more Smart Citation
“…Examples of similarly structured questions seem common in SE. A second systematic review about studies of trade-off decisions in SE came to the same conclusion [13]. Again, data collection in empirical studies was predicated on the narrowly framed concepts of rationalistic decision making: factors, weights, ranking, and choice.…”
Section: The Normative Fallacy In Sementioning
confidence: 94%
“…In behavioral SE studies, however, the normative fallacy appears common. Systematic literature reviews in key areas suggest that many studies in SE use prescriptive theories to collect and interpret data about behavior for descriptive and explanatory purposes [13], [14]. In an extensive systematic literature review on Technical Debt decisions, we found that of the few studies that performed descriptive empirical work, all relied exclusively on rationalistic decision making theories [14].…”
Section: The Normative Fallacy In Sementioning
confidence: 96%
“…Additionally, Becker, Walker, and McCord [40] mapped studies about intertemporal choices -a concept of psychology and behavioral economics referring to "decisions involving tradeoffs among costs and benefits occurring in different times" [41] -in software engineering. They found that no empirical work investigated trade-offs in time in depth.…”
Section: B Padding Estimates To Buy Timementioning
confidence: 99%
“…We note that meta-analysis is only possible when there is a substantial amount of existing research on a subject. Temporal discounting in software engineering has not been extensively studied before [24]. Our chosen strategy is therefore to gradually expand the body of knowledge regarding temporal discounting by first replicating the original observational study design.…”
Section: Replication In Software Engineeringmentioning
confidence: 99%
“…How can we reduce excessive discounting in specific areas such as project management or technical debt? Which assumptions of current methods in these areas need to be revisited [24]? How should the findings influence the creation of new methods for use in industry?…”
Section: Implications For Researchersmentioning
confidence: 99%